2021
DOI: 10.1155/2021/5544835
|View full text |Cite
|
Sign up to set email alerts
|

Microwave Vitrification of Uranium Tailings: Microstructure and Mechanical Property

Abstract: In this work, the dense glass matrix of uranium tailings was successfully fabricated via microwave sintering process with Na2CO3 as a sintering aid. The effects of Na2CO3 additive and sintering temperature on the microstructure and mechanical properties of as-prepared solids were systematically investigated. XRD results confirmed the vitrified forms can be achieved at 1200°C within 30 min with 20 wt.% Na2CO3 addition. Importantly, the Na2CO3 additive significantly reduced the firing temperature from 1500°C to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…They also fulfil specific measurement requirements and enable the accurate assessment of U-wastes and potentially contaminated waste (Clark et al 2003). Characteristics of U-wastes include (Jiang et al 2020(Jiang et al , 2021(Jiang et al , 2022Wei et al 2021;liu et al 2021;Mao et al 2022):…”
Section: Types Of U-wastementioning
confidence: 99%
See 1 more Smart Citation
“…They also fulfil specific measurement requirements and enable the accurate assessment of U-wastes and potentially contaminated waste (Clark et al 2003). Characteristics of U-wastes include (Jiang et al 2020(Jiang et al , 2021(Jiang et al , 2022Wei et al 2021;liu et al 2021;Mao et al 2022):…”
Section: Types Of U-wastementioning
confidence: 99%
“…The results showed that the leaching efficiency of U significantly increased when the wastes were subjected to microwave irradiation along with the composite oxidation of Fe 3 (III) and Mn(VII). (Wei et al 2021) investigated the production of a dense glass matrix of U-waste by microwave sintering. The addition of na 2 CO 3 as a sintering aid lowered the ignition temperature and promoted condensation, resulting in vitrified forms of waste.…”
Section: Recovery Of U-wastementioning
confidence: 99%